Unveiling the efficacy of repetitive transcranial magnetic stimulation in Parkinson’s disease: A comprehensive review of systematic analyses - Lingwen Zhang; Yanhong Jiang; Wenhui Fan; Hua Xue (PLoS ONE, 2025)
Background Many systematic reviews (SRs) have reported the repetitive transcranial magnetic stimulation (rTMS) for Parkinson’ s disease (PD), but the quality of the evidence is unclear. The aim of this study was to summarize the evidence provided by SRs on the effect of rTMS on PD. Methods A comprehensive search for SRs published from the establishment of the library to March 1, 2024, was conducted in PubMed, EMBASE, Cochrane Library, Web of Science, CNKI, VIP and Wanfang databases. The A Measurement Tool to Assess Systematic Reviews 2 (AMSTAR-2), the Risk of Bias for Systematic Reviews (ROBIS), and Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) tool were used to evaluate the methodology quality, risk of bias and evidence quality of SRs, respectively. Results We identified 16 SRs. According to the results of the AMSTAR-2, 12.5% (2/16) of the SRs rated as high quality, 43.75% (7/16) rated as low quality, and 43.75% (7/16) rated as very low quality. Based on the ROBIS tool, 6 (37.5%) SRs had low risk of bias. The GRADE results suggested that 16.13% (10/62) of the evidence was of moderate quality, 33.87% (21/62) of the evidence was of low quality and 50% (31/62) of the evidence was of very low quality. Moderate-quality results show that rTMS can improve PD motor symptoms. Conclusions Here we show that rTMS can improve the motor symptoms of PD, but its effectiveness in treating non-motor symptoms of PD is inconsistent. Due to the methodological limitations and diversity in study designs, future studies should focus on addressing these issues by providing thorough methodological details, standardizing rTMS protocols, evaluating side effects, and comparing with other treatments.